Impact of ASD and ADHD on pediatric asthma exacerbations: a retrospective analysis of the Nationwide Inpatient Sample 2005–2020 - Dai-Xuan Lin; Ya-Ting Chang; Yu-Chun Lo; Shih-Ming Weng (Italian Journal of Pediatrics)
Abstract Background To explore the impact of autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) on in-hospital outcomes in children hospitalized for asthma exacerbations. Methods This retrospective study utilized data from the Nationwide Inpatient Sample (NIS) database between 2005 and 2020. We included children aged 5 to 19 years admitted for asthma exacerbations. Children were categorized into four groups: those with ASD only, ADHD only, both ASD and ADHD, and neither condition. Propensity score matching was used to balance baseline characteristics. Results A total of 155,893 children hospitalized for asthma were identified, with 2,443 patients remaining after propensity score matching. Children with both ASD and ADHD had the highest total hospital costs, followed by those with ASD alone. Children with both ASD and ADHD had significantly increased risks of overall complications (aOR = 1.69, 95% CI: 1.27–2.26), including epilepsy (aOR = 3.56, 95% CI: 1.61–7.87), pneumonia (aOR = 2.00, 95% CI: 1.33–3.03), and constipation (aOR = 4.22, 95% CI: 1.58–11.26), compared to those without either condition. Children with ASD alone also had elevated risks for epilepsy (aOR = 3.79, 95% CI: 1.79–8.03) and constipation (aOR = 4.33, 95% CI: 1.78–10.54). Conclusion In the US children hospitalized for asthma exacerbations, those with both ASD and ADHD, or ASD alone, face significantly greater costs and higher risks of specific complications, particularly epilepsy, pneumonia, and constipation. The findings suggest a compounded impact of these neurodevelopmental conditions on asthma children, emphasizing the need for specialized care to manage these patients effectively and reduce the risks.